Upregulation of OX40 ligand on monocytes contributes to early virological control in patients with chronic hepatitis C. Issue 7 (26th June 2013) - Zhang, Ji‐Yuan; Wu, Xiao‐Li; Yang, Bin; Wang, Yu; Feng, Guo‐Hua; Jiang, Tian‐Jun; Zeng, Qing‐Lei; Xu, Xiang‐Sheng; Li, Yuan‐Yuan; Jin, Lei; Lv, Sa; Zhang, Zheng; et al.
<x xml:space="preserve">Abstract</x> Dysfunctional hepatitis C virus (HCV) specific CD4+ T cells are known to contribute to inadequate adaptive immunity in chronic hepatitis C (CHC), although the underlying mechanisms remain largely undefined. In this study, OX40 ligand (OX40L) expression was investigated in 41 treatment‐naïve CHC patients, 20 sustained virological responders and 36 healthy subjects. We observed that OX40L expression was significantly upregulated in peripheral monocytes in CHC patients compared with sustained virological responders and healthy subjects. OX40L upregulation correlated significantly with plasma viral load rather than serum alanine aminotransaminase levels. Furthermore, longitudinal analyses indicated that upregulated OX40L expression on monocytes is closely associated with rapid or early virological responses in patients receiving pegylated IFN‐α/ribavirin treatment. In vitro, HCV core antigen strongly stimulated monocyte expression of OX40L and blockade of TLR2 signaling significantly downregulated OX40L expression. More importantly, elevated OX40L expression was also shown to be closely associated with elevation of the HCV‐specific CD4+ T‐cell response and in vitro blockade of OX40L expressed on monocytes led to impaired CD4+ T‐cell function. These findings, therefore, implicate OX40L expression can be used as a marker to evaluate antiviral treatment efficacy and extend the notion that enhancement of OX40L expression could be a good way for immunotherapy in CHC patients.